A limited number of double-strand DNA breaks is sufficient to delay cell cycle progression. Issue 19 (3rd September 2018) - van den Berg, Jeroen; G. Manjón, Anna; Kielbassa, Karoline; Feringa, Femke M; Freire, Raimundo; Medema, René H
Abstract: DNA damaging agents cause a variety of lesions, of which DNA double-strand breaks (DSBs) are the most genotoxic. Unbiased approaches aimed at investigating the relationship between the number of DSBs and outcome of the DNA damage response have been challenging due to the random nature in which damage is induced by classical DNA damaging agents. Here, we describe a CRISPR/Cas9-based system that permits us to efficiently introduce DSBs at defined sites in the genome. Using this system, we show that a guide RNA targeting only a single site in the human genome can trigger a checkpoint response that is potent enough to delay cell cycle progression. Abrogation of this checkpoint leads to DNA breaks in mitosis which gives rise to aneuploid progeny.